2022
DOI: 10.3390/s22218196
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Power Issues in Biologging: An Audio/Inertial Recorder Case Study

Abstract: In the past decades, biologging, i.e., the development and deployment of animal-borne loggers, has revolutionized ecology. Despite recent advances, power consumption and battery size however remain central issues and limiting factors, constraining the quantity of data that can be collected and the size of the animals that can be studied. Here, we present strategies to achieve ultra-low power in biologging, using the design of a lightweight audio-inertial logger as an example. It is designed with low-power MEMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Higher current peaks correspond to SD writing events. In a previous study [4], it was observed that SD writing power efficiency improves when large data chunks are stored at once. Therefore, data are always buffered prior to SD writing, with a constant buffer size of 30 SD sectors (15 kB).…”
Section: Embedded Power Consumptionmentioning
confidence: 97%
See 2 more Smart Citations
“…Higher current peaks correspond to SD writing events. In a previous study [4], it was observed that SD writing power efficiency improves when large data chunks are stored at once. Therefore, data are always buffered prior to SD writing, with a constant buffer size of 30 SD sectors (15 kB).…”
Section: Embedded Power Consumptionmentioning
confidence: 97%
“…This MCU is designed around an ARM Cortex-M4 core, featuring a hardware Floating Point Unit (FPU). Further details on hardware choices are provided in [4].…”
Section: Hardware Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…To help, we have included a guide to key SensorDrop device design considerations, potential pitfalls, and resolutions in the device failure sheet in the online repository.When combined with mature wildlife collar technologies from commercial telemetry brands, SensorDrop provides a low-risk system for researchers to innovate upon and test new sensors for wildlife research. The growing accessibility of DIY electronics components (such as SparkFun and Arduino) and the narrowing divide between wildlife researchers and technologists (facilitated by the emergence of online interdisciplinary communities such as WILDLABS) has led to a boom in researcher-developed innovations within the wildlife sciences (e.g., De La Rosa, 2019;Miquel et al, 2022;Wijers et al, 2018). SensorDrop addresses a key barrier to the continued innovation of animal-borne sensors in that it allows specific animal-borne sensors to be cost-effectively remotelydetached and retrieved from wildlife collars.…”
mentioning
confidence: 99%